PENEGAKAN HUKUM TERHADAP ANGGOTA MILITER DALAM PENYALAHGUNAAN NARKOTIKA DI WILAYAH HUKUM PENGADILAN MILITER I -04 PALEMBANG - Muthia Septiana; Erdianto '; Mexsasai Indra (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2015)
Circulation and abuse of narcotics and drugs has reached a very alarminglevel. Criminal act of abuse of drugs has penetrated the military, but they are a majorcomponent in the country's defense system, and an instrument of the state in charge ofmaintaining, protecting and maintaining the integrity of the country, and are expectedto provide an example to the community not to commit criminal acts narkotika.Tujuanthesis This, namely: First, How law enforcement against members of the military indrug abuse in the jurisdiction of the Military Court I-04 Palembang, Second, Constraintenforcement against members of the military in drug abuse in the jurisdiction of theMilitary Court I-04 Palembang, Third, efforts done to overcome obstacles lawenforcement against members of the military in drug abuse in the jurisdiction of theMilitary Court I-04 Palembang.This type of research can be classified into types of sociological research. Thistype of research is descriptive analysis. Source of data used were obtained throughthree (3) legal materials are the primary legal materials, secondary and tertiary. Thedata collection techniques were done using two methods ie interviews and review ofliterature.From the results of research and discussion, there are three main things thatcan be inferred. First, Law Enforcement Against Military Members In Narcotics AbuseIn Military Court has jurisdiction in accordance with the legislation in force and on acase by Case Number: 54-K / PM I-04 / AD / IV / 2014 already meet the elements of acriminal offense military and criminal elements. Secondly, the obstacle in theApplication of Crime of Abuse of Narcotics Law is no internal or external factors suchas: The limited number of members of the Military Police investigators, lack ofInfrastructures, Third, Efforts to Address Barriers In Law Enforcement AgainstNarcotics Abuse Crime: the addition of personnel, make arrests , and do security.Suggestions, first, earned memsosialisasikan Military Law periodically throughmenyuluhan-extension primarily related to narcotic crime, as well as crack down andprocess each infringement. Second, the facility should be sufficient to prove someone isabusing narcotics without having to use the facilities of other agencies. Also added anumber of personnel in the investigation so that information is known to theinvolvement of members of the military. Always hold active operation or sudden raidsheld that the Military Police more find pidanayang acts performed.Keywords: Law Enforcement - Crime - Abuse of Narcotics - Military